Avaliação de Biomarcadores de Estresse Oxidativo em Crianças com Transtorno de Espectro Autista (TEA) - IARA DUENHA GARANHANI (2025)
Autism Spectrum Disorder (ASD) is a neurodivergent condition characterized by deficits in social interaction, communication, and repetitive behaviors, with broad clinical variability. Recent evidence indicates that oxidative stress and inflammation may be involved in the pathophysiology of ASD. In this context, the present study aimed to evaluate oxidative stress and inflammation biomarkers in children diagnosed with ASD. The study included 22 children with ASD (up to 12 years old) and 13 neurotypical children, matched as a control group after approval by the Human Research Ethics Committee of the Federal University of Mato Grosso do Sul (UFMS) (CAAE 70494823.7.0000.0021). Venous blood samples were collected, with and without anticoagulant (EDTA), to obtain serum and whole blood, respectively. The antioxidant enzymes superoxide dismutase (SOD), catalase (CAT) and gamma-glutamyltransferase (GGT), the non-enzymatic antioxidants reduced glutathione (GSH) and uric acid (UA), the inflammatory markers interleukin-1 beta (IL-1β) and myeloperoxidase (MPO), and the markers of oxidative damage, such as thiobarbituric acid-reactive substances (TBARS) and carbonyl protein (PC), were analyzed. Statistical analysis was performed using Student's t-test, considering significance at p < 0.05. The results indicated a significant increase in the activities of SOD (p < 0.001), MPO (p < 0.01), and IL-1β (p < 0.01) in children with ASD, in addition to an increase in the concentration of TBARS (p < 0.05) and PC (p < 0.01). A significant reduction in CAT (p < 0.001) and GGT (p < 0.001) activity, as well as GSH (p < 0.01) and UA (p < 0.05) concentrations were also observed in the ASD group. These findings reinforce the hypothesis of the involvement of oxidative stress and inflammation in the pathophysiology of ASD and suggest that investigating specific biomarkers may contribute to improving diagnostic and therapeutic strategies.